Isolation and sequence analysis of the Chlamydia pneumoniae GroE operon. - Kikuta, L C (1991)
Chlamydia pneumoniae has emerged as an important human respiratory pathogen. From a lambda gt11 gene bank constructed from C. pneumoniae isolate AR-39 DNA, an immunoreactive plaque containing a 3.0-kb insert was purified. In immunoblots, a 60-kDa protein was recognized by anti-C. pneumoniae rabbit immune serum. The recombinant protein was reactive with a Chlamydia genus-specific monoclonal antibody recognizing a 60-kDa protein found in the Sarkosyl-soluble fraction and with rabbit immune serum prepared against the Chlamydia trachomatis 60-kDa GroEL homolog associated with the delayed-type hypersensitivity response. DNA sequence analysis confirmed that the C. pneumoniae gene product is an analog of the C. trachomatis delayed-type hypersensitivity antigen and the Escherichia coli GroEL heat shock protein.